High risk of adrenal insufficiency after a single articular steroid injection in athletes - Duclos, M.; Guinot, M.; Colsy, M.; Merle, F.; Baudot, C.; Corcuff, J. B.; Lebouc, Y. (Medicine & Science in Sports & Exercise, 2007)
Purpose: To determine whether a single intra- or periarticular injection of corticosteroid for posttraumatic or microtraumatic articular injuries in young healthy subjects can induce a biological suppression of hypothalamo-pituitary-adrenal axis activity and reactivity.